Development of the 'Curious Scientist' Game to Practice Scientific Thinking Skills - Hanik Aida; Woro Sumarni; Putut Marwoto; Bambang Subali; Ellianawati Ellianawati (Postgraduate, University of Mataram, 2022)
This study aimed to develop an android-based game learning media by applying the steps of the scientific method. Methods: UsingThe development research was adapted the RnD method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The data collection technique was a validation questionnaire of media experts, linguists, materials, teacher, and student responses. Findings: The validation results of media, language, and material experts were 92.00, 92.00, and 96.00%, respectively, with very feasible criteria. Student response questionnaires in the small and large group trials were 96.00, 94.00, and 89.70%, respectively, with very achievable benchmarks. The teacher's response questionnaire also got more than 80.00%, which was very decent. Conclusion: The result application of the 'Curious Scientist' game learning media is interesting for students. Indirectly, students have learned to use the scientific method approach and apply scientific thinking skills utilizing the learning media game' Curious Scientist.’